A comparison of clinical communication skills between two groups of final-year medical students with different levels of communication skills training - Marietjie R. de Villiers; Martie van Heusden (South African Family Practice)
Background: Training in communication skills is prominent in many undergraduate medical programmes. In South Africa, training in this highly complex skill is developing rapidly, especially against the backdrop of a multilingual and multicultural society. Little work has been done locally to evaluate which training works best in our context. In 1999, the Stellenbosch University Faculty of Health Sciences introduced a new curriculum that included considerably more communication skills training. The aim of this study was to assess and compare the communication skills used in the consultations of two groups of final-year medical students who had different levels of communication skills training in order to make recommendations on appropriate changes in this training.